2012
DOI: 10.1177/000313481207801004
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-Assisted Extralevator Abdominoperineal Resection in the Lithotomy Position: Technique and Early Outcomes

Abstract: Extralevator abdominoperineal resection (E-APR) has been advocated as a superior procedure to achieve negative circumferential resection margins (CRMs) for sphincter-invading rectal cancers. An open total mesorectal excision is performed followed by perineal dissection with resection of the levators in the prone position. We describe a novel minimally invasive robotic approach carried out in the lithotomy position. Using the robotic arms to dissect the rectum and divide the levator fibers at their origin, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…For example, AR, which is technically easy, accounted for a large proportion of robotic surgeries in the initial period because many surgeons were unfamiliar with robotic systems. Since then, ISR and APR have increased to account for higher proportions of robotic surgeries performed, likely because surgeons can operate on rectal tumours with lower and more difficult locations, allowing the technological advantage of a robotic system to be maximized after a learning‐curve . Although there is scant literature that can numerically verify the advantages of robotic surgery over laparoscopic surgery, surgeons might be aware of the best and most cost‐effective surgical indication through experience.…”
Section: Discussionmentioning
confidence: 99%
“…For example, AR, which is technically easy, accounted for a large proportion of robotic surgeries in the initial period because many surgeons were unfamiliar with robotic systems. Since then, ISR and APR have increased to account for higher proportions of robotic surgeries performed, likely because surgeons can operate on rectal tumours with lower and more difficult locations, allowing the technological advantage of a robotic system to be maximized after a learning‐curve . Although there is scant literature that can numerically verify the advantages of robotic surgery over laparoscopic surgery, surgeons might be aware of the best and most cost‐effective surgical indication through experience.…”
Section: Discussionmentioning
confidence: 99%
“…and Kang et al . completed the dissection of the origins of the levator muscles via a transabdominal approach in a robotic‐assisted manner, and Chi et al . performed the same procedure in a laparoscopic‐assisted manner, which did not require any change in positioning during surgery, thus shortening the duration of surgery and reducing the risk of early stoma complications.…”
Section: Discussionmentioning
confidence: 99%
“…14 Performing an APR in the lithotomy position may be advantageous in specific clinical scenarios, such as when posterior rectal visualization is required or when utilizing robotic technology for pelvic dissection. 38,39 Importantly, CRM positivity is an independent risk factor for local recurrence and overall survival in rectal cancer after surgical intervention. 17 On multivariate analysis of risk factors for local recurrence, Tayyab et al demonstrated a hazard ratio of 8.2 for a positive CRM.…”
Section: Discussionmentioning
confidence: 99%